A construção de sentido no gênero charge: O discurso humorístico da crítica social no Brasil nas Eras FHC e Lula - Lima, Marília Dalva Teixeira de (2012)
The construction of the meaning in visual-verbs statements as the cartoons genre occurs in a complex way since this genre of discourse presents a tangle of elements that provide the most diverse meaning effects. This paper aims to analyze how occur the meaning effects which are constructed from the relationship between verbal and nonverbal statements on cartoons genre. The theoretical foundation which subsidizes this study is the Theory of Enunciation proposed by Bakhtin and the Circle, particularly the concepts of dialogism, carnivalization and statements, are also used concepts from Discourse Analysis Guidance French such as formation, discursive memory, discursive happening, and the interdiscourse, establishing dialogues between the dialogic Theory of Discourse, based on Bakhtin, and the Discourse Analysis the base pecheuxtiana. The cartoons which will be used in this research will be by the cartoonist Chico Caruso, published in the newspaper O Globo, between the years 1994 and 2006, portraying two important moments in Brazilian politics: FHC and Lula's era. The study adopts the inductive method of research and about the data approach, follows the paradigm of qualitative research and interpretive. It is characterized also as to the procedures of data collection, such as bibliographic and documentary research. The research results indicate that inserted into a communication context bigger than the face to face interaction, cartoons try to reproduce through symbols recognizable by the reader, the scenario of enunciation, making possible the understanding of the statement included in its historical context, ideological and political, and gender also maintains a constant dialogue with the subject-reader and they have an important role in recorded history.